2014
DOI: 10.1603/me13209
|View full text |Cite
|
Sign up to set email alerts
|

Vacant Lots: Productive Sites forAedes(Stegomyia)aegypti(Diptera: Culicidae) in Mérida City, México

Abstract: We assessed the potential for vacant lots and other non-residential settings to serve as source environments for Aedes (Stegomyia) aegypti (L.) in Mérida City, México. Mosquito immatures were collected, during November 2011 – June 2013, from residential premises (n = 156 site visits) and non-residential settings represented by vacant lots (50), parking lots (18), and streets/sidewalks (28). Collections totaled 46,025 mosquito immatures of 13 species. Ae. aegypti was the most commonly encountered species accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…aegypti oviposition [93] or a restricted class of non-residential sites, such as schools [94, 95]. Consideration of non-residential structures and spaces that sustain oviposition during dry seasons–such as vacant lots [96], septic tanks [97], and drains [98, 99]–is sparse. Although special surveillance of SPs is mandatory in Brazil, the absence of rigorous examination of the importance of SP infestation for dengue virus transmission limits the capacity of municipal actors to take evidence-based steps to improve their routine control activities.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti oviposition [93] or a restricted class of non-residential sites, such as schools [94, 95]. Consideration of non-residential structures and spaces that sustain oviposition during dry seasons–such as vacant lots [96], septic tanks [97], and drains [98, 99]–is sparse. Although special surveillance of SPs is mandatory in Brazil, the absence of rigorous examination of the importance of SP infestation for dengue virus transmission limits the capacity of municipal actors to take evidence-based steps to improve their routine control activities.…”
Section: Discussionmentioning
confidence: 99%
“…For storm-water drains/catch basins, we used long-handled zooplankton nets (20 × 10 cm, 100-μm mesh). More detailed descriptions of the survey methodology were given by Arana-Guardia et al (2014) for storm-water drains/catch basins and Baak-Baak et al (2014) for the other urban environments.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported on the immature or adult stage of the primary local vector mosquito, Aedes ( Stegomyia ) aegypti (L.), for dengue virus. The studies reported on containers and seasonal patterns of abundance for immatures (Lloyd et al 1992; Winch et al 1992; Manrique-Saide et al 2008, 2012, 2013; García-Rejón et al 2011a; Arana-Guardia et al 2014; Baak-Baak et al 2014) and examined different indoor environments for adults (García-Rejón et al 2008, 2011b). Additional studies have reported more broadly on the mosquito fauna of the Yucatán Peninsula (Najera-Vazquez et al 2004, Zapata-Peniche et al 2007, Ortega-Morales et al 2010, García-Rejón et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti mosquitoes in a variety of containers that collect water. 8,9 However, limited information is available about the role of uninhabited houses in Ae. aegypti productivity.…”
Section: Introductionmentioning
confidence: 99%